Por uma ontologia social crítica: considerações sobre o amelhoramento do conceito de mulher nas áreas da metafísica e da pragmática conceitual - Luccas, Gabriela Pedroso (2024)
This work aims to expose the state of the art of the metaphysical discussion on gender categories, focusing on four problems present in this literature: (i) how the improvement of the concept of woman can contribute to the development of feminist metaphysics; (ii) how this literature allows us to clarify issues related to the delimitation and use of the concept of "woman"; (iii) the means by which social ontology allows us to understand the intersections between sex, gender and gender identity; and (iv) the presentation of the minimum conditions for the improvement of the concept of woman and the reasons why the inadequate use of this concept can contribute to social inequalities. In the first chapter, we will examine the work "Gender and Gender Terms" (2019) by Elizabeth Barnes and the externalist perspective of gender, based on Haslanger (2012) and Ásta (2013; 2018). These approaches treat gender as a social system that privileges and oppresses based on social expectations. The works discussed address how gender is a marker of social position. The second chapter addresses the distinction proposed by Katharine Jenkins in “The Amelioration and Inclusion: Gender Identity and the Concept of Woman” (2016), between the concept of “woman” as a class of people and as a feminine identity. Jenkins argues that, for an accurate designation, the concept of woman must exclude those who do not identify with the feminine identity and include those who should be included by the same criterion. The critique focuses on the difficulty of gender theories in providing an adequate and universal definition of what it is to be a woman, man or non-binary person. The third chapter contains three sections that explore different theories and methodologies, in which we analyze contextualist theories and Thomasson’s pragmatic method, and notions of conceptual engineering by Cappelen and Plunkett. The section explores how conceptual engineering can improve the application of gender concepts, proposing to maintain the word “woman” while altering its meaning to better suit the identified functions. This chapter also discusses Kevin Richardson’s (2023) critical perspective on how normative issues and contextual values can produce effective practical interventions. The final chapter examines Kukla and Lance’s “Telling Gender: Pragmatics and Ethics of Gender Ascriptions” (2022), highlighting how gender ascriptions establish social norms and how the use of gender terms is both descriptive and normative. This analysis highlights that, while our study offers an improved understanding of gender concepts, it does not exhaust the discussions pertinent to the metaphysics of gender.